Thermal fluid-structure interaction in the effects of pin-through-hole diameter during wave soldering - M. S. Abdul Aziz; M. Z. Abdullah; C. Y. Khor; Z. M. Fairuz; Muhammad Iqbal Ahmad; Mazlan Mohamed; Mohd Sukhairi Mat Rasat (Hindawi Publishing Corporation, 2014)
An effective simulation approach is introduced in this paper to study the thermal fluid-structure interaction (thermal FSI) on the effect of pin-through-hole (PTH) diameter on the wave soldering zone. A 3D single PTH connector and a printed circuit board model were constructed to investigate the capillary flow behavior when passing through molten solder (63SnPb37). In the analysis, the fluid solver FLUENT was used to solve and track the molten solder advancement using the volume of fluid technique. The structural solver ABAQUS was used to examine the von Mises stress and displacement of the PTH connector in the wave soldering process. Both solvers were coupled by MpCCI software. The effects of six different diameter ratios (0.1 <